Políticas linguísticas e educacionais: o ensino de língua alemã em Marechal Cândido Rondon, Paraná - Martiny, Franciele Maria (2015)
This thesis addresses the teaching of German in Marechal Cândido Rondon, Paraná, Brazil, covering the time from the colonization of the locality, in the beginning of the 1950s, until today. The locality was colonized mostly by German immigrants and descendants coming from Germanic regions in Europe and from the Brazilian states of Rio Grande do Sul and Santa Catarina. Due to this context, the German language was always present in the city, but it has been decreasingly spoken and heard. Recently, the state government has enabled policies for reviving the immigrant languages by offering German courses both in the degree course in Portuguese/German Languages at the local university and in extracurricular classes at CELEM. Nevertheless, the demand of students is minimal and evasion is frequent, threatening the continuity of both courses. Based on this problem, this thesis aims to analyze the language and education policies implemented in the socio-historical and cultural context of that city in order to examine the reason for the state language planning not obtaining positive results in the community. In order to achieve this goal, the epistemological approach in this study is based on interactionism from language studies by the Bakhtin Circle, connected with Applied Linguistics (AL) and Sociolinguistics, focusing on contexts of language and education policies for linguistic minorities. The research methodology, under the interpretive perspective, consists of document analysis on the German teaching in the schools that used to offer it, interviews with teachers, students and directors who participated in various moments of the history of teaching in the locality, and personal experience during research, with quantitative and qualitative data. The results show that the lack of language and education policies for formal teaching of German throughout the local history has contributed to the decline of the immigration language, which was never present in the curriculum at a municipal level, despite the existence of the Municipal Law n. 3922, from 2008, and other Germanic cultural practices. In the case of the existing courses at the university and at CELEM, the factors that influence directly to the non-permanence of students involve teaching and learning methodology, since the immigration language is taught as a foreign language without an effective approach to cultural and local issues, which could deconstruct myths, prejudices and negative attitudes that permeate the contact between languages and their varieties. Therefore, there is the need to set language and education policies through intensive work focused on regional linguistic and cultural diversity in order to minimize the diglossic conflict and promote the strengthening of bilingualism in society with greater community involvement